2001
DOI: 10.1128/jcm.39.10.3578-3582.2001
|View full text |Cite
|
Sign up to set email alerts
|

Direct Identification of Bacteria from Positive Blood Cultures by Amplification and Sequencing of the 16S rRNA Gene: Evaluation of BACTEC 9240 Instrument True- Positive and False-Positive Results

Abstract: In a previous study which evaluated the BACTEC 9240 automated blood culture system (Becton Dickinson Diagnostic Instrument Systems, Sparks, Md.), we noted a 1.3% "instrument false-positive" rate. That is, the BACTEC system signaled that a bottle (BACTEC Plus Aerobic/F bottle or BACTEC Anaerobic Lytic/10 bottle) culture was positive but a Gram stain was negative and there was no growth of bacteria or yeasts on subculture to chocolate agar. Furthermore, from the same sample of blood, cultures for fungi using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…The rates of sequencing failures and no matches were low (1% each). Like other investigators (5,12,22), we also found this approach to be useful in confirming false-positive blood culture results when Gram staining and subculture onto solid media yielded no organisms (data not shown). It is a good idea to incorporate more than one ribosomal gene target into the testing algorithm, as it increases the number of DNA sequences one has to analyze, which can provide a cross check on the data generated and increase your confidence in the accuracy of the organism's identification, if concordance occurs.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The rates of sequencing failures and no matches were low (1% each). Like other investigators (5,12,22), we also found this approach to be useful in confirming false-positive blood culture results when Gram staining and subculture onto solid media yielded no organisms (data not shown). It is a good idea to incorporate more than one ribosomal gene target into the testing algorithm, as it increases the number of DNA sequences one has to analyze, which can provide a cross check on the data generated and increase your confidence in the accuracy of the organism's identification, if concordance occurs.…”
Section: Discussionmentioning
confidence: 51%
“…Several sequence-based approaches have been successfully used to identify bacteria directly from positive blood culture bottles. Qian et al successfully used the MicroSeq 500 kit (Perkin-Elmer Applied Biosystems, Foster City, CA), a commercially available method that sequences the first 527 bases of the amplified 16S rRNA gene, for this purpose (22). Turenne et al used single-stranded conformation polymorphism analysis of PCR amplicons to distinguish between organisms (23), while Peters et al used fluorescence in situ hybridization to identify pathogens out of positive blood cultures (19).…”
mentioning
confidence: 99%
“…Although it is considered the gold standard, culturing blood can generate false-negative results up to 31% of the time and false-positive results up to 10% of the time, [1][2][3][4] making confirmation by PCR desirable. Achieving accurate PCR results from blood culture samples is difficult, however, because of the presence of sodium polyanetholsulfonate (SPS), a powerful PCR inhibitor that is added routinely to blood culture media to i) lower the barrier for bacterial growth by inhibiting the complement pathway, ii) prevent blood coagulation, and iii) interfere with the activity of some antibiotics.…”
mentioning
confidence: 99%
“…The contamination rate in the present study was 2.8% which lies within the accepted contamination value and is low in comparison with contamination rates of 1.21 -13.6% reported by other studies. 11,13,16,21,22 Mortality from fungal infections in intensive care units is reported to be 38 -75% and, in recent years, there has been an increase in the rates of fungal infections with nosocomial origins. 41 -43 Most of these involve Candida spp, of which 48% of are Candida albicans.…”
Section: Discussionmentioning
confidence: 99%